Pengaruh Komitmen Terhadap Kinerja Pegawai Negeri Sipil Di Kota Pekanbaru - Novita, Novita (Jurnal Daya Saing, 2016)
Civil Servants are employees were seen from the financial establishment, as judged That this employee has a relatively high salary and plus allowances and health insurance, education and old age security. The issue of the performance of civil servants still in the spotlight, which, although he had done civil service reform, but at lower levels of service to the community still felt alone is not optimal. Some literature states that this is due to a lack of commitment to provide public services under the notabenenya no money and just a lot of complaining. This research was conducted in the Parliament Secretariat Pekanbaru City as a base for the people's voice, this study used a sample of 56 people with census methods, data were collected by questionnaire and analyzed using simple linear regression analysis. The study says that the commitment of a significant effect on the performance of employees. This proves that the employee committed in serving the community, the better the performance achieved in the country devoted to this. Keywords: Employee Performance, Commitment